201k views
0 votes
Please select the best answer from the choices provided

A
B
C
D

Please select the best answer from the choices provided A B C D-example-1

2 Answers

3 votes

the answer is D simply................


User Rella
by
5.1k points
4 votes
ANSWER

The correct answer is D.


\sum_(n=1) ^(6) (n - 3) = ( - 2) + ( - 1) + (0) + (1) + (2) + (3) = 3

Step-by-step explanation

The given expression is


\sum_(n=1) ^(6) (n - 3)

The symbol means summation.

So we need to substitute


n=1,n=2,n=3,n=4,n=5, \:and\:n=6

into the formula and add all to get,


\sum_(n=1) ^(6) (n - 3) = (1 - 3) + (2 - 3) + (3- 3) + (4 - 3) + (5 - 3) + (6 - 3)

We simplify to obtain,


\sum_(n=1) ^(6) (n - 3) = ( - 2) + ( - 1) + (0) + (1) + (2) + (3) = 3

The correct answer is D
User Yaron
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.